2016
DOI: 10.1039/c6sc02116f
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum nitride films integrated with transparent conductive oxide substrates via atomic layer deposition for photoelectrochemical water splitting

Abstract: The first example of tantalum nitride electrodes on transparent conductive oxide substrates, which enables solar water splitting, is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 44 publications
(41 reference statements)
4
57
0
2
Order By: Relevance
“…[7] To date,t here have been few reports of PEC oxygen evolution using transparent Ta 3 N 5 -based photoanodes.H ajibabaei et al recently reported at ransparent Ta 3 N 5 photoanode prepared on aT a-doped TiO 2 -coated SiO 2 (Ta-TiO 2 / SiO 2 )s ubstrate. [8] This Ta 3 N 5 /Ta-TiO 2 /SiO 2 photoanode showed excellent transparencya bove the 600 nm absorption edge wavelength of Ta 3 N 5 ,although the photocurrent density produced by this photoanode at 1.23 Vv s. RHE was 0.8 mA cm À2 . [8] Thus,t he development of high-performance transparent Ta 3 N 5 -based photoanodes for use in tandem PEC cells remains challenging.Thef abrication of transparent Ta 3 N 5 films is not at rivial task, largely due to the extreme conditions required to prepare Ta 3 N 5 .T a 3 N 5 -based photoanodes are typically processed by heating Ta precursor compounds in an NH 3 atmosphere at high temperatures (close to 1000 8 8C).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…[7] To date,t here have been few reports of PEC oxygen evolution using transparent Ta 3 N 5 -based photoanodes.H ajibabaei et al recently reported at ransparent Ta 3 N 5 photoanode prepared on aT a-doped TiO 2 -coated SiO 2 (Ta-TiO 2 / SiO 2 )s ubstrate. [8] This Ta 3 N 5 /Ta-TiO 2 /SiO 2 photoanode showed excellent transparencya bove the 600 nm absorption edge wavelength of Ta 3 N 5 ,although the photocurrent density produced by this photoanode at 1.23 Vv s. RHE was 0.8 mA cm À2 . [8] Thus,t he development of high-performance transparent Ta 3 N 5 -based photoanodes for use in tandem PEC cells remains challenging.Thef abrication of transparent Ta 3 N 5 films is not at rivial task, largely due to the extreme conditions required to prepare Ta 3 N 5 .T a 3 N 5 -based photoanodes are typically processed by heating Ta precursor compounds in an NH 3 atmosphere at high temperatures (close to 1000 8 8C).…”
mentioning
confidence: 83%
“…[8] This Ta 3 N 5 /Ta-TiO 2 /SiO 2 photoanode showed excellent transparencya bove the 600 nm absorption edge wavelength of Ta 3 N 5 ,although the photocurrent density produced by this photoanode at 1.23 Vv s. RHE was 0.8 mA cm À2 . [8] Thus,t he development of high-performance transparent Ta 3 N 5 -based photoanodes for use in tandem PEC cells remains challenging.Thef abrication of transparent Ta 3 N 5 films is not at rivial task, largely due to the extreme conditions required to prepare Ta 3 N 5 .T a 3 N 5 -based photoanodes are typically processed by heating Ta precursor compounds in an NH 3 atmosphere at high temperatures (close to 1000 8 8C). [5a,g, 6-9] Unfortunately,f ew visible-light-transparent, electrically conductive substrate materials can survive such conditions.Inthe present work, we employed n-type GaN-coated double-sidepolished sapphire (GaN/Al 2 O 3 )s ubstrates (that do not degrade in NH 3 at high temperatures [10] )a st he substrate.…”
mentioning
confidence: 83%
“…After first-time growth, substrates were again repeatedly drop cast with Sb:SnO 2 solution, annealed in af urnace, and etched in acetic acid one more time to make the Sb:SnO 2 nanotube arrays with thicker walls. [60] 0.622.1 BiVO 4 (Flat-T8-BV) 0.213 0.62 CuWO 4 (compact) [61] 0.121.1 a-Fe 2 O 3 (host-guest) [62] 0.091 1.5 Ta 3 N 5 (compact) [63] 0.095 0.79 a-Fe 2 O 3 (compact) [64] 0.023 0.32…”
Section: Atonanotube Synthesismentioning
confidence: 99%
“…Allerdings leiden herkçmmliche Oxide wie etwa TiO 2 ,WO 3 und ZnO aufgrund ihrer breiten Bandlücke unter unzureichenden Lichtsammeleigenschaften. [10] All diese Materialien zeigen vielversprechende Ergebnisse,j edoch steht ihre Erforschung noch immer am Anfang.T rotz signifikanter Fortschritte in diesem Bereich [8,[11][12][13] verbleiben einige Beschränkungen wie etwa Kosten, Stabilitäti nS äure/Base und Ladungstrennungseffizienz. Dennoch liegen die so erhaltenen Photostrçme aufgrund der starken Rekombinationsverluste im Volumen nach wie vor weit unterhalb der theoretischen Grenze.…”
Section: Introductionunclassified
“…[4][5][6][7][8] In jüngster Zeit sind auch zahlreiche andere Halbleitermaterialien fürP EC in den Fokus gerückt, darunter Oxidnitride, [9] Metallchalkogenide [9] und kohlenstoffbasierte Materialien. [10] All diese Materialien zeigen vielversprechende Ergebnisse,j edoch steht ihre Erforschung noch immer am Anfang.T rotz signifikanter Fortschritte in diesem Bereich [8,[11][12][13] verbleiben einige Beschränkungen wie etwa Kosten, Stabilitäti nS äure/Base und Ladungstrennungseffizienz.…”
Section: Introductionunclassified